Implementasi Moderasi Beragama Dan Implikasinya Terhadap Sikap Inklusif Di Paguyuban Ananda Tahun 2023/2024 - Reza Arya Pradana (Departement of Mathematics Education, 2023)
Paguyuban Ananda is a Buddhist religious organization whose members come from various cross-border councils in Buddhism. The differences that exist require the right strategy to unite so that there is no conflict that can divide groups within one sphere of society. Steps that can be taken are to form an attitude of Religious Moderation. Religious moderation has an important role in forming an inclusive attitude between religious communities. Moderation is an attitude of understanding differences and eliminating extreme or excessive attitudes (Saifudin, 2019:15). Harmony and balance in social life is one of the efforts to strengthen religious moderation so that the implementation of religious moderation becomes the first step in creating an attitude of implication for Religious Communities (Religious Research and Development and Training Agency of the Ministry of Religion of the Republic of Indonesia, 2019: 120).The method used in this research is the qualitative phenomenological method, in phenomenological research there are main characteristics, namely (a) referring to reality, in this case awareness of a clear object, (b) understanding the meaning of events and their relationships to people who are in certain situations, (c) start with silence. Based on a phenomenological view, researchers try to understand the meaning of events and their relationships to ordinary people in certain situations. The use of a phenomenological approach is intended to describe symptoms or phenomena that appear as they really are, Moleong (2010: 8). Then the researcher collected data from each person, namely the three respondents who experienced the phenomenon, and developed a combined description of the essence of the experience for all individuals. The description developed consists of